2023
DOI: 10.3390/brainsci13060887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Physical Activity in Families Managing ADHD and the Cyclical Effect on Worsening Mental Health

Erica Seal,
Julie Vu,
Alexis Winfield
et al.

Abstract: Physical activity supports symptom management in children with ADHD and reduces the mental health burden associated with caregiving for children with ADHD. Survey-based research shows that COVID-19 reduced physical activity among diverse populations. This study used a qualitative approach situated within a socioecological framework to (1) understand how COVID-19 impacted physical activity of children with ADHD and their caregivers, to (2) identify barriers to their physical activity, and to (3) identify potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
(167 reference statements)
0
2
0
Order By: Relevance
“…In the domain of adult education, specifically, it is evident that COVID-19 has worsened social inequalities and brought them into sharper focus, having implications for the well-being and mental health of these particular groups [ 32 , 131 , 132 , 133 , 134 ]. Moreover, regarding the factors of self-esteem and self-efficacy and the anti-COVID-19 measures, some studies did not find significant changes in the levels of those factors among the participants between anti-COVID-19 measures or afterward [ 135 ]. However, other studies have recorded lower levels of self-efficacy in underage students [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the domain of adult education, specifically, it is evident that COVID-19 has worsened social inequalities and brought them into sharper focus, having implications for the well-being and mental health of these particular groups [ 32 , 131 , 132 , 133 , 134 ]. Moreover, regarding the factors of self-esteem and self-efficacy and the anti-COVID-19 measures, some studies did not find significant changes in the levels of those factors among the participants between anti-COVID-19 measures or afterward [ 135 ]. However, other studies have recorded lower levels of self-efficacy in underage students [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…PA beneficially impacts both brain structures and functions [ 21 , 22 , 23 ]. A study found decreases in the thickness of the prefrontal cortex and parahippocampal cortex in physically active children compared to inactive children [ 24 ].…”
Section: Introductionmentioning
confidence: 99%